2005
DOI: 10.1007/s00467-005-1944-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin-angiotensin system in the development of the ureteric bud and renal collecting system

Abstract: Genetic, biochemical and physiological studies have demonstrated that the renin-angiotensin system (RAS) plays a fundamental role in kidney development. All of the components of the RAS are expressed in the metanephros. Mutations in the genes encoding components of the RAS in mice or pharmacological inhibition of RAS in animals or humans cause diverse congenital abnormalities of the kidney and lower urinary tract. The latter include renal vascular abnormalities, abnormal glomerulogenesis, renal papillary hypop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
34

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 86 publications
0
23
0
34
Order By: Relevance
“…This opposite effect of AT 1 and AT 2 receptors, namely a stimulatory effect of AT 1 and inhibitory effect of AT 2 , is also described on other tissues (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This opposite effect of AT 1 and AT 2 receptors, namely a stimulatory effect of AT 1 and inhibitory effect of AT 2 , is also described on other tissues (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 75%
“…ANGII and AT 2 receptor antagonist treatment induced an increase in lung branching by the stimulation of p44/42 and Akt phosphorylation. These intracellular mediators are also involved in AT 1 effects on proliferation and survival of cells in other tissues (34,36). Regarding lung growth inhibition induced by AT 1 antagonist, it was mediated by a decrease of p-38 and JNK phosphorylation.…”
Section: Discussionmentioning
confidence: 98%
“…Immunoreactive AT1 was decreased at 78 dG, whereas renin was increased in the RC kidneys at dG 135 but not at 78 dG. Previous authors have suggested AT1 as an important mediator of branching morphogenesis in the fetal kidney (34). Others have demonstrated dysregulation of the intrarenal RAS in rat models of programmed hypertension (8,17,35,36).…”
Section: Discussionmentioning
confidence: 92%
“…The RAS was accepted to have a role in kidney development, with a role in vasculogenesis, branching morphogenesis and development of hypertension in the adult, as the result of a reduction in nephron number during nephrogenesis (7,36).…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%